Contribuição ao Estudo Químico de Espécies do Estado do Ceará: Heliotropium indicum Linn, Heliotropium polyphyllum Lehm e Ganoderma lucidum - Souza, João Sammy Nery de (2009)
This work reports the phytochemistry study of two species of the genus Heliotropium: H. indicum Linn and H. polyphyllum Lehm, and of the macrofungal Ganoderma lucidum, collected in the State of Ceará. The analysis of the essential oils from aerial parts’ of the species of Heliotropium, for different extraction techniques, allowed the identification of different secondary metabolic, from hydrocarbons, terpenoids, alcohols even sesquiterpenoids. For the essential oil from roots OEHI all 17 constituents chemicalents were identified and the fitol (49,10%) were the major compound. The phytochemistry investigation from etanolic extract of the roots of H. indicum resulted in the isolation, among others compounds, one pirrolizidine alkaloid that has been named as helindicine (HI-2). The phytochemistry study from extract etanolic for aerial parts’ of H. polyphyllum allowed the isolation of the alkaloid licopsamine (HP-1). The chromatographic analysis of the fixed constituints from etanolic extract of Ganoderma lucidum allowed the isolation of the steroids ergostane: ergosta-7,22,-dien-3-one, ergosta-22-en-3,4,8-triol, ergosta-1,4,8(14),22-tetraen-3-one, and the mixture of ergosta-5,9,22-trien-3-ol and ergosta-5,22-dien-3-ol. A series of derived from steroid ergosta-7,22-dien-3-one was developed starting from the modification in the carbon C-3 with obtaining of alcohols, steres (formil and acetil) and oxima. The structural determination of all natural products, and derived was performed by mean of spectroscopic techniques such MS, IR, 1H and 13C NMR, including uni and bi-dimensional pulse sequences. The identification of the volatile constitution was performed by GC/MS for the qualitative analysis while GC/FID was used for the quantitative analysis, and still comparison to data published in the literature was also used for identification wherever the case.